Enhancement of scan-line polygon filling algorithm - Agutaya A. Jennifer P. and Barnachea A. Lilibeth. 4 0 16; 5 (2002)
u
Undergraduate Thesis: (BSCS major in Computer Science) -Pamantasan ng Lungsod ng Maynila, 2002.
Keywords: 2 -- 0; 6; 20; 20; 2